A 2023 update on the performance of ionic-liquid proton-exchange-membrane fuel cells - East, Allan L. L.; Nguyen, Cuong M.; Hempelmann, Rolf (Frontiers in Energy Research, 2023)
A mini-review is provided of the literature concerning the performance of proton-exchange-membrane fuel cells (PEMFCs) containing (immobilized) ionic liquids (ILs) as possible electrolytes, focusing on papers reporting performance metrics (power and current densities). For over a decade, and especially for Combined Heat and Power Applications, there has been a drive to design an ionic-liquid-holding membrane that could operate well in non-humidifying (water-free) conditions above 100°C. Such a goal has not yet been achieved: reported power densities are still below those of traditional low-temperature fuel cells. Progress has been slow. Other recent reviews have already pointed to three main issues: poor conductivity, poor cathode (oxygen-reduction) kinetics, and seepage of the liquid from the membrane. Here, we use performance metric data to highlight the lack of improvement in the past 5 years, summarize which IL-PEMFC systems have performed the best so far, and attempt to improve the understanding of their conductivity mechanisms. It is hoped that the improved description of the Grotthuss H+ relays will aid in the design of IL-PEMs with improved conductivity.